2011
DOI: 10.1128/aem.02321-10
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Distribution, and Diversity of Salmonella enterica in a Major Produce Region of California

Abstract: A survey was initiated to determine the prevalence of Salmonella enterica in the environment in and around Monterey County, CA, a major agriculture region of the United States. Trypticase soy broth enrichment cultures of samples of soil/sediment (n ‫؍‬ 617), water (n ‫؍‬ 252), wildlife (n ‫؍‬ 476), cattle feces (n ‫؍‬ 795), and preharvest lettuce and spinach (n ‫؍‬ 261) tested originally for the presence of pathogenic Escherichia coli were kept in frozen storage and later used to test for the presence of S. en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
210
6
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(242 citation statements)
references
References 46 publications
22
210
6
4
Order By: Relevance
“…Addis et al (30) reported that Salmonella strains isolated from fecal and milk samples of dairy cattle were resistant to ampicillin (100%), streptomycin (66.7%), and nitrofurazone (58.3%) and sensitive to ciprofloxacin (91.7%), clotrimazole (87.5%), and cephaxon (75%). Gorski et al (25) stated that Salmonella isolates were sensitive to 12 different antibiotics. Wieczorek and Osek (24) stated that some of the S. Dublin, S. Enteritidis, and S. London strains were resistant to sulfamethizole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addis et al (30) reported that Salmonella strains isolated from fecal and milk samples of dairy cattle were resistant to ampicillin (100%), streptomycin (66.7%), and nitrofurazone (58.3%) and sensitive to ciprofloxacin (91.7%), clotrimazole (87.5%), and cephaxon (75%). Gorski et al (25) stated that Salmonella isolates were sensitive to 12 different antibiotics. Wieczorek and Osek (24) stated that some of the S. Dublin, S. Enteritidis, and S. London strains were resistant to sulfamethizole.…”
Section: Discussionmentioning
confidence: 99%
“…Cattle are the most important Salmonella reservoir agents and consumption of infected cattle meat is related to salmonellosis epidemics (25). Various studies were carried out to isolate and serotype Salmonella from dairy cattle and calves (4,7,14,18,21,22,24).…”
Section: Discussionmentioning
confidence: 99%
“…Although established methods for detecting EHEC and Salmonella are readily available (11,12,21), the specific methods used by the third-party company were not disclosed. Generally, however, the company's pathogen testing procedure consists of DNA preparation, amplification, and detection.…”
Section: Methodsmentioning
confidence: 99%
“…Both pathogens are carried by domestic animals (e.g., cattle) and wildlife; however, whereas S. enterica is readily isolated from many wildlife hosts (10,11), EHEC is generally more prevalent in cattle than in wildlife. In one study, for example, 37.9% of cattle vs. only 7.4% of wildlife samples obtained from California's Central Coast tested positive for EHEC (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation